The Impact of Fear of Missing Out (FOMO) on Online Consumer Behaviour: A Theoretical Study of Social Media Users - Neha; Walia, Pardeep Singh (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Fear of Missing Out (FOMO) has emerged as a powerful psychological phenomenon in the digital age, particularly among social media users. This theoretical paper explores how FOMO shapes and influences online consumer behaviour, including impulse buying, peer-influenced purchasing, brand engagement, and digital loyalty. Drawing upon theories such as Social Comparison Theory, Self-Determination Theory, and Uses and Gratifications Theory, the study presents a conceptual framework that links FOMO to various online purchasing behaviours. The paper also discusses the role of social media platforms in amplifying FOMO through algorithm-driven content, real-time peer updates, and targeted advertising. By synthesizing current literature, this study contributes to understanding the psychological mechanisms through which FOMO drives digital consumerism and suggests avenues for future empirical research and marketing strategies that consider ethical implications.